CRITERIA FOR PREDICTING DIABETIC NEPHROPATHY IN CHILDREN WITH TYPE 1 DIABETES MELLITUS (Conferencea, 2023)
Diabetic nephropathy is the most common cause of death in patients with type 1 diabetes. The complexity of the pathogenesis, long-term asymptomatic course and untimely diagnosis lead to unsatisfactory effectiveness of pathogenetic therapy for diabetic nephropathy. According to epidemiological screening, the true prevalence of diabetic nephropathy exceeds the actual one by 2 - 4 times. The high medical and social significance of diagnosing diabetic nephropathy in patients with type 1 diabetes mellitus explains the large number of works devoted to this topic. Over the past decades, given the development of new laboratory methods, the standards for diagnosing kidney pathology of diabetic origin have changed. Modern screening tests make it possible to detect diabetic nephropathy only from the stage of microalbuminuria , while the initial morphofunctional disorders that develop long before the increase in urinary albumin excretion are missed. The earliest signs of kidney damage can be detected already in the first 5 years from the onset of type 1 diabetes. According to a number of researchers, it is during this period that the initiation of preventive measures to prevent the progression of DN can be most effective. All of the above determines the relevance of searching for early non-invasive markers for the preclinical diagnosis of diabetic nephropathy.